2020
DOI: 10.4236/wjcd.2020.104017
|View full text |Cite
|
Sign up to set email alerts
|

Oxidase Enzyme Activities and Their Correlations with Antioxidative Stress Biomarkers in Patients with Acute Coronary Syndrome in Bangladesh

Abstract: Acute coronary syndrome (ACS) is a range of conditions associated with decreased blood flow in the coronary arteries resulting from sudden rupture of atherosclerotic plaques. Several studies have found that oxidative stress is involved in the initiation and progression of atherosclerosis. The role of oxidase enzymes and antioxidative stress biomarkers in these processes needs further attention. In this study, a total of 120 participants were enrolled which comprised 60 ACS patients and 60 control subjects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
0
1
Order By: Relevance
“…As reported by other workers (Messner and Bernhard, 2014;and Messerli et al, 2017), the present study found smoking and previous history of hypertension to be significantly higher in patients with ACS who were screened to exclude those suffering from diabetes mellitus, and any other chronic inflammatory disorder to avoid false-positive results. In contrast to a recent investigation (Ferdausi et al, 2020), this study found a significant association between breathlessness and family history of CVD in the development of ACS. However, the patients enrolled in this study were already hospitalized and being treated with antihypertensive drugs; thus, the observed blood pressure and pulse rate might not be the same as the time of MI attack.…”
Section: Discussioncontrasting
confidence: 99%
“…As reported by other workers (Messner and Bernhard, 2014;and Messerli et al, 2017), the present study found smoking and previous history of hypertension to be significantly higher in patients with ACS who were screened to exclude those suffering from diabetes mellitus, and any other chronic inflammatory disorder to avoid false-positive results. In contrast to a recent investigation (Ferdausi et al, 2020), this study found a significant association between breathlessness and family history of CVD in the development of ACS. However, the patients enrolled in this study were already hospitalized and being treated with antihypertensive drugs; thus, the observed blood pressure and pulse rate might not be the same as the time of MI attack.…”
Section: Discussioncontrasting
confidence: 99%
“…Жүрөк-кан тамыр оорулары медициналык технологиядагы жана дарылоодогу жетишкендиктерге карабастан, дүйнө жүзү боюнча ооруканага жаткыруу жана өлүмдүн негизги себеби болуп калууда (Manckoundia et al, 2017). Атап айтканда, жүрөк-кан тамыр ооруларынын таралышы өнүккөн жана өнүгүп келе жаткан өлкөлөрдө да өсүп, аларды олуттуу глобалдык ден-соолукка тынчсыздандырууда (Ferdausi et al, 2020). Көптөгөн тобокелдик факторлор жүрөккан тамыр ооруларына, анын ичинде гипертония, диабет, семирүү жана тамеки тартууга өбөлгө түзөт.…”
Section: аннотацияunclassified
“…
Cardiovascular diseases continue to be the leading cause of hospitalization and mortality worldwide, despite advancements in medical technology and treatments (Manckoundia et al, 2017). In particular, the prevalence of cardiovascular diseases is increasing in both developed and developing countries, making them a significant global health concern (Ferdausi et al, 2020). Numerous risk factors contribute to cardiovascular diseases, including hypertension, diabetes, obesity, and smoking.
…”
mentioning
confidence: 99%
“…The NADPH oxidase (NOX) activity was measured according to the method established by Reusch and Burger [15], as detailed previously [16]. Briefly, a cocktail (450 μL) was prepared with phosphate buffer, nano-pure water and EDTA (4:4:1).…”
Section: Measurements Performedmentioning
confidence: 99%